Evaluation of clinical research priorities in Asian intensive care units (ERA‑ICU) - Li, Andrew; Nasa, Prashant; Myatra, Sheila Nainan; Shrestha, Gentle Sunder; Al-Fares, Abdulrahman; Chan, Ming-Cheng; Cho, Young-Jae; Egi, Moritoki; Faruq, Mohammad Omar; Harmouche, Carine; Hashemian, Seyed Mohammad Reza; Kharaba, Ayman; et al. (Springer Nature, 2025)
Background: Practice and delivery of critical care in Asia varies according to healthcare structure, income setting, and cultural factors. Identifying research priorities specific to ICU patients and healthcare workers in Asia is needed to guide advancement of critical care in the region. Methods: This was an international cross-sectional survey study with adapted methods from nominal group techniques. All members of the Asian Critical Care Clinical Trials (ACCCT) Group were invited to submit research question suggestions. Submitted research questions were combined into summarized research questions, grouped into research themes, and individually ranked by number of mentions based on the original question submission (popularity). National and Regional Representatives rated the top 15% most popular summarized research questions by pre-defined importance and feasibility criteria. Results: Between September 20, 2024 and December 10, 2024, 160 of 228 general members of the ACCCT Group (response rate 70.2%) participated in this survey study. The participants were from 112 hospitals across 24 countries and regions within Asia. Participants submitted 408 research questions, which were categorized into 15 themes and combined into 197 summarized research questions. The top three themes, as ranked by the number of mentions, were infection/sepsis, general ICU care, and structure/ training/ staffing/ teamwork/ safety. A threshold of 4 mentions was used to identify 26 summarized research questions that represented the top 15% most popular questions. Research questions related to sepsis and acute respiratory distress syndrome were ranked most important and feasible across the region. Conclusion: Twenty-six of the most popular research questions in critical care were identified by Asian ICU workers and researchers to drive research agenda in Asia for the next decade.